A Survey on personnel knowledge and Manometers Precision Applied in Jahrom's Educational Healthcare Centers & Hospitals - Zarei, Safar; Ranjbar, Afsaneh; Abedi, Hassanali; sadeghi, Najmeh (Journal of Neonatal Surgery, 2025)
Background: Blood Pressure Measurement(BPM) is a basic matter of public healthcare concern and one of the most routine tests carried out at clinics. The present study aimed at evaluating knowledge of health care providers and blood pressure manometers precision at Jahrom healthcare centers and hospitals. Materials and methods: The present study was conducted on the basis of a descriptive – cross-sectional study through standardized questionnaires prepared by the researcher, to evaluate the knowledge of 302 cases about how to work with devices and all of 34 the apparatuses accuracy used in measuring blood pressure were at clinics and educational hospitals round Jahrom County between 2019 to 2020. Data was analysed with spss 25. Results: From among the total 34 devices under the study used at clinics and hospitals for measuring blood pressure, there were 13 aneroid gauge (38.23%), 20 mercury-gravity (58.82%), and 1 electronic manometers (2.94%). Among them 13 mercury-gravity and 7 aneroid gauge devices were deficit (Fisher exact test 2= 1.43, p=0.72) . Also 11 mercury and 7 aneroid were out of order which a great share of malfunctions observed to be the outcome of problematic check valves(Fisher exact test 4=1.16, p=0.85. Furthermore, only about 40.20% of general physicians and even a lower percent of nurses and nurse aides ( 17.50%)were aware of correct method of using apparatuses applied in blood pressure measurement(Fisher exact test 1= 17.58, p=0.002). Conclusions: all centers under the study could not be reliable in addition to the fact that users were totally ignorant of either deficiencies of the devices or lack of their knowledge.